Serum Nitrogen and Carbon Stable Isotope Ratios Meet Biomarker Criteria for Fish and Animal Protein Intake in a Controlled Feeding Study of a Women's Health Initiative Cohort. Issue 12 (17th September 2018) - Yun, Hee Young; Lampe, Johanna W; Tinker, Lesley F; Neuhouser, Marian L; Beresford, Shirley A A; Niles, Kristine R; Mossavar-Rahmani, Yasmin; Snetselaar, Linda G; Van Horn, Linda; Prentice, Ross L; O'Brien, Diane M
ABSTRACT: Background: Natural abundance stable isotope ratios are candidate biomarkers of dietary intake that have not been evaluated in a controlled feeding study in a US population. Objectives: Our goals were to evaluate dietary associations with serum carbon (CIR), nitrogen (NIR), and sulfur (SIR) isotope ratios in postmenopausal women, and to evaluate whether statistical models of dietary intake that include multiple isotopes and participant characteristics meet criteria for biomarker evaluation. Methods: Postmenopausal women from the Women's Health Initiative ( n  = 153) were provided a 2-wk controlled diet that approximated each individual's habitual food intake. Dietary intakes of animal protein, fish/seafood, red meat, poultry, egg, dairy, total sugars, added sugars, sugar-sweetened beverages (SSBs), and corn products were characterized during the feeding period with the use of the Nutrition Data System for Research (NDS-R). The CIR, NIR, and SIR were measured in sera collected from fasting women at the beginning and the end of the feeding period. Linear models based on stable isotope ratios and participant characteristics predicted dietary intake. The criterion used for biomarker evaluation was R 2   ≥ 0.36, based on the study's power to detect true associations with R 2  ≥ 0.50. Results: The NIR was associated with fish/seafood intake and met the criterion for biomarker evaluation ( R 2   = 0.40). The CIR was moderately associated with intakes of red meat and eggs, but not to the criterion for biomarker evaluation, and was not associated with intake of sugars (total, added, or SSB). A model of animal protein intake based on the NIR, CIR, and participant characteristics met the criterion for biomarker evaluation ( R 2  = 0.40). Otherwise, multiple isotopes did not improve models of intake, and improvements from including participant characteristics were modest. Conclusion: Serum stable isotope ratios can, with participant characteristics, meet biomarker criteria as measures of fish/seafood and animal protein intake in a sample of postmenopausal women. This trial was registered at clinicaltrials.gov as NCT00000611.